THE CISTOPHORI, DIONYSUS, AND THE VOODOO CULT OF DAMBALLAH (Salduie, 2025)
The knowledge of common iconography, rituals and religious concepts, very similar, between the Greco-Roman cult of Dionysus-Bacchus and that of Damballah, the voodoo spirit that manifests itself as a snake in both Haiti and Louisiana, has led us to highlight these circumstances in this work. The main objective is to point out the parallels, despite the difficulty that the Dionysian cults are of a mysterious nature and those referring to Damballah and his wife Aida, in the early times, those that provide the most information, were secret. Even so, we have highlighted what has been possible for us and that they share, to a greater or lesser degree, both religions. To the similarities between the mystical basket from which a snake emerges, represented in the cistophori, and the snake that is found in a box and taken out for the ritual, in Haiti, are added the very similar iconography of the snakes represented in the reverses of the cistophori with those of Damballah and Aida in voodoo. The staging of carnal union with the serpent, and the development of orgies with sex and alcohol, are also common elements between the Dionysian-Bacchic and the cult of Damballah.
Keywords: Dionysus and Bacchus; Damballah and Aida; mystic snakes; carnal communion; bacchic and voodoo rituals; iconography